To the temple of tranquility... and step on it! : a memoir - Begley, Ed, Jr (Hachette Books, 2023)
The beloved American actor and environmental activist shares humorous and heartfelt stories throughout his life and illustrious career, focusing on his relationship with his legendary father, adventures with Hollywood icons, addiction and recovery and his constant search for wisdom and common ground.